Technoeconomic Evaluation of Cell Site Power Consumption Reduction Using Free Cooling Technique - Boakye, Kojo; Adu, Shiphrah O.; Nunoo, Solomon; Boakye, Kwaku (European Scientific Journal, ESJ, 2024)
Air Conditioning (AC) is the primary source of cooling in a typical Cell Site (CS) although it consumes a great deal of electricity. Excessive energy consumption due to air conditioning increases the operational expenses of telecommunication companies. Therefore, network operators have attempted a variety of techniques to reduce the exorbitant cost associated with a cell site’s high-power consumption. A Free Cooling System (FCS) is one such approach. Using computer modeling, this paper investigated how the FCS will function at a CS in Ghana. The study was conducted for 12 hours (from 6 pm to 6 am). A shelter with dimensions is 3 m × 2.47 m × 2.45 m (L × B × H) is used in the study, with three window positioning scenarios (different window heights) namely: an inlet window is 0.5 m high, and the outlet window is 1.5 m high, an inlet window and outlet window are both 1.0 m high and an inlet window is 1.5 m high, and the outlet window is 0.5 m high. The analysis revealed that a shelter with inlet and outlet windows at the same height has the most efficient heat dissipation potential. Furthermore, at a set temperature threshold of 25 °C, the annual percentage share for the two operating modes is approximately 67% for Air Conditioning (AC) and 33% for Free Cooling (FC) in 2020, 76% for AC and 24% for FC in 2021, and 61% for AC and 39% for FC in 2022. However, when the set temperature threshold is increased from 25 °Cto 30 °C, the annual percentage share is approximately 0.01% for AC and 99.9% for FC in 2020, 0% for AC and 100% for FC in 2021, and 1% for AC and 99% for FC in 2022, thus the proportion of free cooling increases as the set temperature threshold is raised. An indication of energy savings. It can be determined that when FC is operated at a set temperature threshold of 30 °C or higher, most cell sites in Ghana will save a considerable amount of energy.